Yinchenhao Decoction ameliorates the high-carbohydrate diet induced suppression of immune response in largemouth bass (Micropterus salmoides). Issue 125 (June 2022) - Zhao, Liulan; Liang, Ji; Liu, Hao; Gong, Chenxin; Huang, Xiaoli; Hu, Yifan; Liu, Qiao; He, Zhi; Zhang, Xin; Yang, Song; Rahimnejad, Samad
Abstract: Yinchenhao Decoction (YD), a Chinese herbal medicine, has been traditionally used for treatment of metabolic liver diseases. A 10-week feeding trail was carried out to examine the effects of YD supplementation in a high carbohydrate diet (HCD) on liver histopathology, immune response, disease resistance, and expression of genes associated with endoplasmic reticulum stress, autophagy, apoptosis, necroptosis and inflammation in juvenile largemouth. A diet containing 9% carbohydrate was used as a low carbohydrate diet (LCD), and a HCD was formulated to contain 18% carbohydrate and supplemented with 0, 0.5, 1, 2 or 4% YD (HCD, HCD+0.5YD, HCD+1YD, HCD+2YD and HCD+4YD). Triplicate groups of fish (5.6 ± 0.2 g) were feed the test diets to visual satiety for 10 weeks. The highest survival rate after Nocardia seriolae challenge was recorded for the HCD+4YD group. YD application led to reduced ACP, AKP, AST and ALT activities. HCD-induced cells swelling, ruptured cell membrane, migrated nuclei and increasing inflammatory cells in hepatocytes were mitigated by YD addition. Moreover, YD decreased the expressions of pro-inflammation genes ( TNF-α, IL-1β, IL-8, hepcidin1, NF-κB, COX2, CD80 and CD83 ) and increased the mRNA levels of anti-inflammation genes ( IL-10 and IKBα ). The mode of liver cell death was preferably changed to programed apoptosis rather than uncontrolled necroptosis by application of YD in HCD. Furthermore, the expression of UPR genes ( IRE1, Eif2α, ATF6, XBP1 and GRP78/Bip ) and autophagy genes ( LC3-2, BNIP3 and P62 ) was increased by YD supplementation. In summary, our results demonstrated that YD addition in HCD enhances UPR, autophagy and programed apoptosis maintaining the homeostasis, and decreases uncontrolled necroptosis and inflammation, ultimately leading to improved immune response in largemouth bass. Highlights: YD promoted the UPR and autophagy to maintain hepatocytes intracellular homeostasis balance of largemouth bass fed HCD. YD promoted programmed apoptosis rather than pro-inflammatory necroptosis to remove damaged hepatocytes. YD improved the immunity and decreased hepatic inflammation in largemouth bass.